PENGARUH PENAMBAHAN EKSTRAK BAWANG MERAH (Allium cepa) DALAM PENGENCER TRIS - KUNING TELUR TERHADAP KUALITAS SPERMATOZOA SAPI BALI PADA PENYIMPANAN IN VITRO (The effect of additional onion (Allium cepa) extract in tris - egg yolk extender on the sperm... - Fian K. Djita; Wilmientje M. Nalley; Thomas M. Hine; Aloysius Marawali (Universitas Nusa Cendana, 2021)
The purpose of this study was to determine the effect of adding onion extract (OE) to Tris-egg yolk (T-EY) diluent on the quality of bali bulls spermatozoa. The semen of three bali bulls aged 3-4 years were collected twice a week using the artificial vaginal method. Semen with good quality, motility 79%, viability 84.63%, abnormality 2.93% diluted with T-EY diluent with the addition of OE: T0: 0%; T1 1%; T2: 2%; T3: 3%; T4: 4%; and T5: 5%. The diluted semen was preserved in a refrigerator at 3-5 °C and evaluated for the quality of the spermatozoa every 24 hours. The results showed that the addition of OE in T-EY diluent had a positive effect on the quality of bali bulls spermatozoa. The addition 3% of OE (T3) in T-EY diluent resulted in higher spermatozoa quality (P <0.05) than the other treatments, namely motility 42.01%, viability 48.74%, and abnormalities 4.13% on the sixth day of preservation. It was concluded that the addition of onion extract in Tris - egg yolk diluents could improve the quality of bali bulls spermatozoa, with the best level of onion extract being 3%.